1996
DOI: 10.1046/j.1365-2141.1996.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of allogeneic bone marrow transplantation from an HLA‐identical sibling or a matched unrelated donor in the treatment of children with juvenile chronic myeloid leukaemia

Abstract: Seven children (age range 1.8-11 years) with juvenile chronic myelomonocytic leukaemia (JCML) received an allogeneic bone marrow transplantation (BMT), four from an HLA-identical sibling and three from a matched unrelated donor. In the four children transplanted using an HLA-identical sibling, conditioning regimen included busulfan (BU), cyclophosphamide (CY) and melphalan (L-PAM), whereas graft-versus-host disease (GVHD) prophylaxis consisted of cyclosporine-A (Cs-A). The preparative regimen was well tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…[5][6][7][8][9][10][11] However, the results concerning prognostic factors after SCT were not necessarily clear partly because of inaccuracy of the diagnosis. It was not until recently that the disease entity of JMML was established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] However, the results concerning prognostic factors after SCT were not necessarily clear partly because of inaccuracy of the diagnosis. It was not until recently that the disease entity of JMML was established.…”
Section: Discussionmentioning
confidence: 99%
“…Niemeyer et al 4 reported that the probability of survival at 10 years was 39% for patients who received bone marrow transplantation (BMT) and 6% for patients who did not receive it. Allogeneic BMT was frequently employed in this disease, [5][6][7][8][9][10][11] but interpretation of the results was difficult due to variability in conditioning regimens, type of donors, and pretransplant therapy. In addition, it was also complicated by the inaccur- acy of the diagnosis in the past: patients of other myelodysplastic disorders seemed to be included in JMML.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of tailoring a preparative regimen for SDS patients by adding a second alkylating agent was based on the results of a preliminary study demonstrating the safety of combining melphalan with busulfan 30 and on the fact that the retrospective analysis of the EWOG-MDS group showed that a myeloablative preparative regimen including a second alkylator was associated with a better event-free survival (EFS) and a lower relapse rate in comparison with regimens including TBI. 31 Similarly, poorer results of HSCT for SDS-associated myelodysplasia/acute leukemia have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid sustained engraftment in 20 of 22 evaluable children proved that engraftment was not a problem, similar to results in other studies. 14,15,17,22 Factors possibly predicting a relapse, as found by us and by others, relate to karyotype, 14 intensive pre-BMT chemotherapy, conditioning regimen, 11,22 donor type, 11 TCD and GvHD. 15 Manabe et al 14 found in a multivariate analysis on the outcome of 27 JMML patients an abnormal karyotype to be the only significant risk factor for decreased OS.…”
Section: Discussionmentioning
confidence: 99%
“…The BU, CY and melphalan (Mel) regimen, used from December 1996 onwards, was proposed by Locatelli et al 17 Three patients received the CY/TBI-based regimen in this period because of pre-existent hepatic dysfunction. TBI was given as a single fraction of 7-7.5 Gy to patients younger than 10 years, and in two fractions of 6 Gy each on two consecutive days to children aged X10 years.…”
Section: Conditioning Regimensmentioning
confidence: 99%